A taxonomic revision of the tarantula spider genus Coremiocnemis Simon 1892 (Araneae, Theraphosidae), with further notes on the Selenocosmiinae - West, Rick C.; Nunn, Steven C. (Zootaxa, 2010)
The selenocosmiine genus Coremiocnemis Simon 1892 is revised for the first time with six new species included. Five new species are from West Malaysia: C. brachyramosa sp. nov. from Gunung Ledang, Johor; C. gnathospina sp. nov. and C. hoggi sp. nov. from Fraser’s Hill, Selangor; C. jeremyhuffi sp. nov. from Tapah, Perak, Fraser’s Hill, Selangor to Pahang and C. obscura sp. nov. from Taiping, Perak to Cameron Highlands, Pahang. C. kotacana sp. nov. is described from Aceh Teneggara, Sumatra, being the first record of this genus outside Malaysia or Australia. A lectotype and paralectotype are designated for C. cunicularia (Simon 1892). All but two of Abraham’s non-type C. valida Pocock 1895 (Abraham 1924) specimens held in both the NHM and RMBR are newly transferred to C. cunicularia. Abraham’s two remaining specimens are removed from Coremiocnemis. C. valida is redescribed, its former dubious locality is resolved. Zoogeographic considerations of all species are discussed and resolved. Ontogenetic variation within Coremiocnemis is discussed. Several new characters are introduced. Subfamilial relationships with proposed sister genera Selenocosmia Ausserer 1871 and Lyrognathus Pocock 1895 are discussed. A key to species is provided.